ANALISIS TINGKAT KINERJA PENANGGULANGAN COVID-19 DI STIKES AWAL BROS PEKANBARU - Nadiah Salsabila; Marido Bisra (LPPM Universitas Awal Bros, 2021)
At the beginning of 2020, the world was shocked by the outbreak of a new pneumonia disease originating from Wuhan, China. The outbreak was named coronavirus disease 2019 (COVID-19) and caused the disease Coronavirus Disease2019 (COVID-19). However, on January 16, 2022, the Pekanbaru City Health Office stated that Pekanbaru City had entered PPKM level 1. There were already several schools and universities that had started face-to-face lectures. Therefore, the purpose of this study was to analyze the level of performance in handling covid-19 at the Stikes Awal Bros Pekanbaru campus. This study uses the Importance Performance Analysis (IPA) method which is included in quantitative descriptive research which then the data can be processed using SPSS. The target of this research is all students of Stikes Awal Bros Pekanbaru. The results of the research that we can describe in accordance with the Cartesian diagram are the results of the study showing that there are 2 attributes that we must maintain and 3 attributes that we must improve their performance in dealing with Covid-19 at STIKes Awal Bros Pekanbaru.